IOT-BASED MOBILE MANIPULATOR PROTOTYPE USING ESP 32 AND ESP 8266 - Revassy, Rosalina N; Suparno; Ramadhana, Dwi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research focuses on the design and implementation of an Arduino-based mobile robot equipped with an ESP32 camera. The primary goal is to develop a mobile manipulator prototype that can be controlled remotely via a mobile or web application. This project also aims to identify the required electronic components, understand their integration with the ESP32 module, and evaluate the ESP32's advantages over the Arduino Uno. The method used is a development research approach, involving literature review on robotics, Arduino programming, and image processing with the ESP32-CAM and ESP8266. The research stages include system design, component selection, mechanical design, and electronic circuit design. Programming code development is carried out iteratively, starting with basic functions such as motor movement and image capture, to more complex functions such as simple object recognition. Testing of the mobile manipulator prototype demonstrates that the hardware and software developed are functional. The robot is capable of motion control, image transmission from the ESP32-CAM to a smartphone, and the ESP8266 can transport light objects. However, there are several challenges, such as overheating of the ESP32-CAM and ESP8266 modules, as well as potential malfunctions in the SG90 servo motor and DC gearbox motor.